Futuristic Trends in Network and Communication Technologies : First International Conference, FTNCT 2018, Solan, India, February 9–10, 2018, Revised Selected Papers /: First International Conference, FTNCT 2018, Solan, India, February 9–10, 2018, Revised Selected Papers. (2018) - Unknown
No abstract available